2021
DOI: 10.1039/d1cp02617h
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous nucleation of sheared liquids: advances and insights from simulations and theory

Abstract: One of the most ubiquitous and technologically important phenomena in nature is the nucleation of homogeneous flowing systems. The microscopic effects of shear on a nucleating system are still imperfectly...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 195 publications
0
7
0
Order By: Relevance
“…The shear-CNT formalism reported by Goswami et al, 30 which incorporates the analytical theory reported by Mura and Zaccone, 15 results in an efficient methodology for predicting nucleation trends under shear at high pressure in comparison to forward flux sampling and brute force simulations. 42,43 3. Simulation details…”
Section: Methodology Sequencementioning
confidence: 99%
“…The shear-CNT formalism reported by Goswami et al, 30 which incorporates the analytical theory reported by Mura and Zaccone, 15 results in an efficient methodology for predicting nucleation trends under shear at high pressure in comparison to forward flux sampling and brute force simulations. 42,43 3. Simulation details…”
Section: Methodology Sequencementioning
confidence: 99%
“…This same trend was observed for the conditions with different shear rates, where the condition at 0.2 s −1 showed the highest number of crystals for both bulk and surface crystallization. Recent theoretical and experimental studies 25,[32][33][34]54,55 have suggested that an increase in the stirring speed of melts can in fact increase the crystal nucleation rates. Although our results indicate the opposite trend, this could be a consequence of the Ostwald ripening phenomenon.…”
Section: Crystallization In Dynamic Conditionsmentioning
confidence: 99%
“…In the meantime, the influence of shear flow on nucleation has also been studied theoretically. First, it is suspected that shear has a positive effect on nucleation rate due to the enhancement of mass transport, inducing an increase of the kinetic nucleation rate prefactor, which has been proven experimentally in a Taylor–Couette flow device. , At a low shear rate, Allen et al . also suggested that shear-induced coalescence of nuclei could take place.…”
Section: Introductionmentioning
confidence: 98%
“…Shear may also induce the molecular alignment, enhancing the nucleation rate, , which is particularly true for polymer crystallization. , Second, at high shear rates, it is suspected that a negative effect on nucleation rate predominates. It has been suggested that shear induces small elastic deformations of the nucleus, which in turn increases the free energy barrier and/or leads to shear-mediated nucleus breakup. ,, From these competitive effects, it is supposed that a nucleation rate maximum exists. While such a maximum has been theoretically identified for colloids , or for ice crystallization, , to our knowledge experiments on real molecular systems are elusive.…”
Section: Introductionmentioning
confidence: 99%